Factors Influencing School Preference: Mapping the Student Market - Archie Carlo U. Cruz; Aira Mae M. Salamatin; Ken Paul M. Espinosa (Future Science / FSH-PH Publications, 2025)
The study aimed to explore the students’ insights by examining the factors that influence their school preference and overall experience during the enrollment process. The study utilized a descriptive-quantitative research method employing survey research to analyze the perspectives of incoming college students. The participants of the study were all admitted students for the school year 2024-2025 at Baliuag University, Baliwag City, Bulacan. Specifically, the study employed a nonprobability sampling technique known as purposive sampling. A total of 707 respondents were involved in the conduct of the investigation, which comprised the total number of students who answered the survey questionnaire. The students’ school preference, based on the results of the study, spans factors not limited to advertising strategies. With friends’ and relatives’ recommendations being the most influential, this underscored the importance of the respondents’ social groups in choosing their university for higher education pursuits. Along with this factor are programs offered, academic excellence/quality education, mode of transportation being tricycle, sportsfest, and learning modality preferred as face-to-face classes. Further, the outstanding enrollment process satisfaction results also indicated that the institution should continuously maintain its current operational techniques as well as its openness to feedback, as service quality proved to be fundamental in how students perceive higher education institutions. The findings of the study served as a basis for targeted recommendations aimed at continuously improving university positioning in the student market, proactively responding to evolving student preferences, and ensuring relevance in the highly competitive Philippine higher education institution academic landscape.